2019
DOI: 10.1021/acs.jpclett.9b00382
|View full text |Cite
|
Sign up to set email alerts
|

Delocalization and Quantum Entanglement in Physical Systems

Abstract: Quantum coherence and entanglement in an extended interacting system where energy levels are nondegenerate and coupled to a dissipative environment is a common occurrence in nature, like in photosynthetic reaction systems and conjugated polymers. The temperature dependence of quantum coherence in a trimer complex (first three subunits of the Fenna–Matthews–Olson complex) is studied using a temperature-dependent quantum stochastic Liouville equation. In the non-Markovian limit, the lowering of temperature induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…We have used the temperature-independent QSLE to study efficient energy transfer dynamics. In our earlier studies, we have shown that the effect of temperature is pronounced in the intermediate coupling regime and explain its effect on the energy relaxation and equilibrium population in the absence of trapping and radiative decay. We also have observed earlier that the inclusion of temperature slows down the excitation energy relaxation dynamics.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…We have used the temperature-independent QSLE to study efficient energy transfer dynamics. In our earlier studies, we have shown that the effect of temperature is pronounced in the intermediate coupling regime and explain its effect on the energy relaxation and equilibrium population in the absence of trapping and radiative decay. We also have observed earlier that the inclusion of temperature slows down the excitation energy relaxation dynamics.…”
Section: Discussionmentioning
confidence: 81%
“…This is a nonperturbative method. We have discussed and employed this approach in our previous studies. ,, We consider that fluctuations around each chromophore are spatially uncorrelated. That is, the fluctuating elements in the Hamiltonian at each chromophore site are independent of each other.…”
Section: Qsle Approachmentioning
confidence: 99%
See 3 more Smart Citations